Influence of Supplementary Blue and Far-Red Light on the Morphology and Texture of Ocimum basilicum L. Grown in Controlled Environments - Madison A. Oehler; Nathan Kelly; Jorge M. Fonseca; Ella Evensen; Eunhee Park; Ganyu Gu; Zi Teng; Yaguang Luo (Horticulturae)
Basil (Ocimum basilicum L.) is highly sensitive to environmental conditions and is an ideal candidate for cultivation in controlled environment agriculture (CEA). Light-emitting diode technology has become essential in CEA, offering precise control over light intensity, spectrum, and duration. This study investigated how supplemental blue light, far-red light, or their combination influences basil biomass, morphology, texture, and color when added to a white + red light spectrum. Basil ’Prospera’ and ’Amethyst’ were exposed to five light treatments for 14–28 days: white + red at 180 µmol∙m−2∙s−1 (W) as the control, and four treatments with an additional 60 µmol∙m−2∙s−1 of either white + red (+W60), blue (+B60), far-red (+FR60), or a combination of B and FR (+B30+FR30), for a total photon flux density of 240 µmol∙m−2∙s−1. The results demonstrated that +B60 and +W60 light treatments increased leaf thickness by 17–20% compared to the +FR60 treatment. Conversely, texture analysis revealed that +FR60-treated leaves had higher puncture resistance, with ’Amethyst’ and ’Prospera’ requiring 1.57 ± 0.43 N and 1.45 ± 0.35 N of force, respectively, compared to 1.19 ± 0.32 N and 1.1 ± 0.21 N under +B60. These findings suggest that tailored light recipes in CEA can optimize basil quality, allowing growers to modify traits like leaf color, thickness, and toughness.